The Efficacy of Gesture on Second Language Pronunciation: An Exploratory Study of Handclapping as a Classroom Instructional Tool. Issue 4 (3rd June 2020) - Iizuka, Takehiro; Nakatsukasa, Kimi; Braver, Aaron
Abstract: In this study, we examined the efficacy of gestures for the acquisition of L2 segmental phonology. Despite teachers' frequent use of gestures in the classroom to teach pronunciation, the field lacks empirical support for this practice. We attempted to fill this gap by investigating the effects of handclapping on the development of L2 Japanese segmentals (long vowels, geminates, and moraic nasals). We assigned L1 English university students in beginning Japanese courses to one of two groups where they practiced pronouncing the targets with or without handclapping in the classroom. They also completed picture elicitation (production) and dictation (perception) tasks as pretests, immediate posttests, and delayed posttests. The results show that, on the delayed perception posttest, only those who saw and performed handclapping maintained the instructional effect, indicating that the memory‐enhancing effect of gestures, at least in the form of handclapping, might reach the level of segmental phonology in L2 acquisition. Abstract :